Transcending the Surface: The Body as a Rhetorical and Ideological Enunciator in the Documentary Noticias - Silva-Oyaneder, V (UNIV PITTSBURGH, UNIV LIBRARY SYSTEM, 2017)
The text raises a critical interpretation about the representation of the body in the documentary Noticias (2009) of the Chilean directors Bettina Perut and Ivan Ossnovikof. To this end, it is emphasize on the capacity of the concept of a body without organs to destroy the intellectual reflection that has been universally hegemonic when it comes to appreciating a work of art. In this way, it is argued that the body in the analyzed film, aims to the dehierarchization of the gaze in the intellectual act of appreciating cinematographic work. The body understood, then, as a sensitive organicity that inverts the reflection of body/intellect, shows the capacity of making a critique of the classic cinematic representation and a questioning to the ideological and social configuration in which, historically, the cinema has developed its discourse.